Folliculitis decalvans and lichen planopilaris phenotypic spectrum: a case series of biphasic clinical presentation and theories on pathogenesis. (1st January 2020) - Yip, L.; Barrett, T. H.; Harries, M. J.
Summary: We present a series of 13 patients with clinical and histological features of both folliculitis decalvans (FD) and lichen planopilaris (LPP), either concomitantly, or sequentially as the clinical phenotype changed over time. This biphasic presentation of FD‐LPP is not as uncommon as would be expected from the lack of description in the literature. We discuss current theories about the pathogenesis of both LPP and FD, and speculate how abnormal immune responses may either predispose to secondary bacterial infection or be influenced by dysbiosis of the skin/hair follicle microbiome, resulting in inflammation and permanent hair follicle damage.